Separable reversible encrypted data hiding in encrypted image using AES Algorithm and Lossy technique - Kadam, P.; Nawale, Mangesh; Kandhare, Akash; Patil, M. (2013 International Conference on Pattern Recognition, Informatics and Mobile Engineering (PRIME), 2013)
The field steganography is very much popular technique for sending secrete message and lots of research are going in it. To overcome the limitation of previous work we proposed separable and reversible encrypted data hiding in encrypted image using AES Algorithm and Lossy technique as solution. In this sender encrypt data and image separately using AES algorithm, hides encrypted data in encrypted image using LSB technique, system auto generate the all 3 respective keys. Sender sends the file through existing mail system. Receiver can perform operation as per respective keys like if he has only data hiding and image decryption key then he can only get the image in original form or if he have data hiding and data decryption key then he can get original data, system also provides protection for auto generated keys and system auto generate mail if user fail to perform any operation.